2012
DOI: 10.1002/mds.25149
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment in Parkinson's disease: Expanding the nonmotor phenotype

Abstract: The objective of this study was to evaluate hearing impairment in patients affected by Parkinson's disease compared with hearing scores observed in normal age- and sex-matched controls. One hundred eighteen consecutive patients with a clinical diagnosis of Parkinson's disease were screened. Severity of motor symptoms and staging were measured with the Unified Parkinson's Disease Rating Scale (section III) and the Hoehn and Yahr scale. Audiometric evaluation consisted of a comprehensive audiologic case history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 35 publications
9
69
2
3
Order By: Relevance
“…Four PD patients and one ART were not included in our data analysis because of middle ear disease revealed by the acoustic impedance test The PD group, by history, showed a mean disease duration of 8.7 ± 1.1 years and, on clinical examination, a mean UPDRS III score of 9.64 ± 5.6 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], H&Y staging ranged from 1.5 to 3 (mean 2.4 ± 1.2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four PD patients and one ART were not included in our data analysis because of middle ear disease revealed by the acoustic impedance test The PD group, by history, showed a mean disease duration of 8.7 ± 1.1 years and, on clinical examination, a mean UPDRS III score of 9.64 ± 5.6 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], H&Y staging ranged from 1.5 to 3 (mean 2.4 ± 1.2).…”
Section: Resultsmentioning
confidence: 99%
“…Hearing impairment frequently occurs in PD patients, and may therefore be considered in the wide spectrum of NMS [4]. Several lines of evidence suggest that hearing impairment may not only be due to the physiological presbycusis that occurs with aging, but could instead originate from a damage involving either the cochlea or the MOC, with a consequent impairment between dopaminergic and glutamatergic neurotransmission below the inner hair cells (IHC) [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of PD was shown to be 1.77 times more likely in patients with hearing loss than in those without nonhearing loss (Lai et al 2014), and hearing impairment is a common feature in idiopathic PD (Vitale et al 2012). …”
Section: Hearing Neuronsmentioning
confidence: 99%
“…The measurement of the evoked potential (EP) is a widely used noninvasive technique for studying the functional changes in neural conductive pathway of PD. Some studies demonstrated VEP or BAEP in patients with PD, but the results were inconsistent (Deng, Deng, Zhao, Yan, & Chen, 2006; Li, 2004; Venhovens, Meulstee, Bloem, & Verhagen, 2016; Vitale et al., 2012; Yylmaz et al., 2009). So our study explored whether the impairment of brainstem auditory and visual passageway exists in patients with PD using VEP and BAEP.…”
Section: Introductionmentioning
confidence: 99%